The predictive validity of the Five-Factor Model of personality with preschool age children: A nine year follow-up study☆ - Abe, Jo Ann A (Journal of Research in Personality, 2005)
This study examined whether maternal ratings of the Five-Factor Model (FFM) obtained when children were 3.5 years would show theoretically coherent patterns of relations with a variety of behavioral referents in the laboratory at 5 years as well as with maternal and self-ratings of psychological functioning in adolescence. As expected, Agreeableness and Conscientiousness were associated with measures of self-regulation at both ages as well as with an internal locus of control, but only Conscientiousness was associated with high academic performance. By contrast, Neuroticism was associated with measures of anxiety and Extraversion was associated with difficulty inhibiting behaviors at both ages. Openness to Experience was associated with sophisticated play behavior at 5 years and self-confidence in adolescence. Overall, this study yielded strong support for the predictive validity of the FFM with preschool age children and provided further evidence that there are striking continuities in personality from early childhood to adolescence. (c) 2004 Elsevier Inc. All rights reserved.
52 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/072-295-048-962-659 tex.type: [object Object]
Keywords: dept.psy; peer-reviewed